2005
DOI: 10.1158/1055-9965.epi-04-0637
|View full text |Cite
|
Sign up to set email alerts
|

Association of Susceptibility Alleles in ELAC2/HPC2, RNASEL/HPC1, and MSR1 with Prostate Cancer Severity in European American and African American Men

Abstract: Reported associations of ELAC2/HPC2, RNASEL/HPC1, and MSR1 with prostate cancer have been inconsistent and understudied in African Americans. We evaluated the role of 16 sequence variants in these genes with prostate cancer using 888 European American and 131 African American cases, and 473 European American and 163 African American, controls. We observed significant differences in ELAC2, RNASEL, and MSR1 allele frequencies by race. However, we did not observe significant associations between prostate cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 39 publications
4
82
1
Order By: Relevance
“…In 2003, Xu et al (10) reported that these three common SNPs (PRO3, IVS-59, and P275A) were significantly associated with prostate cancer risk [PRO3: OR, 1.81; 95% confidence interval (95% CI), 1.15-2.85; IVS-59: OR, 1.73; 95% CI, 1.10-2.72; P275A: OR, 1.75; 95% CI, 1.05-2.94] among 301 cases and 250 controls of Caucasian descent. However, the remaining studies including the current one failed to replicate these findings for PRO3 (11)(12)(13)(14), IVS5-59 (6,11,13,14), and P275A (5,6,(11)(12)(13)15). The different findings between Xu et al (10) and our research may result from study design (hospital-based case-control study versus nested case-control study), time period (unspecified versus 1993-2000), differences in local linkage disequilibrium patterns, and sample size (301 versus 700 cases).…”
Section: Discussionmentioning
confidence: 83%
“…In 2003, Xu et al (10) reported that these three common SNPs (PRO3, IVS-59, and P275A) were significantly associated with prostate cancer risk [PRO3: OR, 1.81; 95% confidence interval (95% CI), 1.15-2.85; IVS-59: OR, 1.73; 95% CI, 1.10-2.72; P275A: OR, 1.75; 95% CI, 1.05-2.94] among 301 cases and 250 controls of Caucasian descent. However, the remaining studies including the current one failed to replicate these findings for PRO3 (11)(12)(13)(14), IVS5-59 (6,11,13,14), and P275A (5,6,(11)(12)(13)15). The different findings between Xu et al (10) and our research may result from study design (hospital-based case-control study versus nested case-control study), time period (unspecified versus 1993-2000), differences in local linkage disequilibrium patterns, and sample size (301 versus 700 cases).…”
Section: Discussionmentioning
confidence: 83%
“…9,10,11 In a retrospective case series, Gronberg et al reported higher grade tumors and more advanced stage at the time of diagnosis in 33 HPC1-linked families compared to 44 unlinked families with hereditary prostate cancer defined by early age of onset, multiple affected family members, or affected men in 3 generations. 9 In a retrospective study, Goode et al reported higher rates of aggressive disease defined as either Gleason score ≥ 7 or advanced clinical stage (Whitmore-Jewett Stage C or D) in a subset of 505 affected men linked to HPC1.…”
Section: Discussionmentioning
confidence: 99%
“…3 Prior case-control and cohort studies have suggested that linkage of HPC1 or presence of the 462Q variant in prostate tumors is associated with early age of onset 7,8 and some have suggested that these tumors present with more aggressive clinical features as measured by tumor grade or clinical stage. 9,10,11 No prior studies have assessed disease severity associated with the R462Q variant in radical prostatectomy specimens. Since the identification of the association between the R462Q variant and prostate cancer susceptibility, we have prospectively collected clinical, pathological, and genotypic information on men undergoing radical prostatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Rennert et al (17) reported a significant increase in risk among African American harboring the genotype Arg/Gln + Gln/Gln with family history. Wang et al (18) and Nakazato et al (19) showed the protective effect of Gln/Gln in Caucasians and Japanese, respectively.…”
mentioning
confidence: 99%